The dichotomous function of interleukin-9 in cancer diseases - Gerlach, Katharina; Weigmann, Benno (Journal of Molecular Medicine, 2019)
The pleiotropic function of the cytokine IL-9 is so far described in many inflammation processes and autoimmune diseases. But its role in cancer immunology is rather diverse as it can have a pro-tumorigenic function as well as anti-tumorigenic characteristics. In various disease models of cancer, this cytokine is involved in different signaling pathways triggering the expression of proteins involved in cell growth, migration, and transformation or repressing cells from the adaptive immune system to reject tumor growth. Additionally, there are even therapeutic approaches for IL-9 in cancer development. This review will give an overview of the various roles of IL-9 in different immune organs and cells and provide an insight in the current state of research in the IL-9-dependent cancer area.
CRIS-Team Scopus Importer:2019-08-16
Keywords: Anti-tumorigenic role; IL-9; Pro-tumorigenic role; Therapy